(untitled) (Medico Legal Update, 2021)
Introduction: Radio diagnosis service plays a crucial role in diagnosis of the patient’s disease. The volume of patients utilising this service is very high. This service also takes away the sizeable share of total capital investment and therefore, the optimal utilization of this service becomes important. Methodology: Literature review was done through Google scholar, electronic database of PubMed and other relevant databases. The query terms like Utilization Review of Imaging Equipment, Utilisation of CT Scanners, Capacity of Scanners in Radiology and Waiting Times for Imaging were used to fetch the relevant data sources. Around 130 articles were reviewed and analysed. Results: The number of CT Scans per 1 million of population in High Income (HI), Upper Middle Income (UMI), Lower Middle Income (LMI) are 14.7, 7.3, 3.7. The CT scanners are one of the most expensive pieces of medical equipment in hospitals, with CT scanners costing between 1 million (?7 crore) and 2 million (?14 crore). There is a substantial variation in the utilisation of these services, including number of scans per day and wait times. Increasing the scanner efficiency and utilisationcan significantly decrease the cost per scan and increase access to imaging services. Expanding capacity, improving operating procedures by reducing change-over times, and improving capacity allocation in combination with scheduling procedures can contribute to the overall reduction of CT access time. Discussion and Conclusion: By acquiring Utilization data about CT Scanners, we get to know a complete and accurate overview of how Scanners are used. The CT scanner utilisation can be improved in both public and private health sector by analysingthe key information about the utilisation of their own and other health services’ CT scanners.